Characterization of Nata De Coco-Benedict Film by Adsorption as Sensor for Glucose in Urine Sample - Dwi Indarti; A Asnawati (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2011)
Research on nata de coco utilization as a film to immobilize benedict reagent for glucose analysis has been conducted. Immobilization of benedict by nata de coco film was evaluated by using adsorption method and characterization i.e. physical characterization (morphology) and viability characterization of its sensors activity for glucose. Morphological characterization (SEM) showed that the benedict reagent has been absorbed by nata de coco film despite leaching activity of 14.7%, with optimum concentration of Benedict of 0.2682 M, 40 min dyeing time at maximum of 541 nm. Sensor characterization of cellulose nata-Benedict for glucose showed regression coefficient of 0.9895, the detection limit of 780 ppm with a sensitivity of 0.001 and adsorption reproducibility of 0.2013%. Glucose content measurement on urine sample by using Nata De Coco-Benedict based Film Nelson-Somogyi.